Painful ophthalmoplegia in a patient with a history of marginal zone lymphoma - C. Van Bogaert; C. Mathey; I. Vierasu; N. Trotta; L. Rocq; A. Wolfromm; V. De Wilde; S. Goldman (European Journal of Hybrid Imaging, 2021)
Abstract A 73-year-old man with a history of marginal zone lymphoma was admitted to the emergency room for diplopia and ipsilateral headache. The Fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) demonstrated intense and symmetrical hypermetabolism of the cavernous sinuses, and hypermetabolic lesions diffusely in the lymph nodes and bones. The diagnosis of high-grade relapse of lymphomatous disease was made. In this context, the homogenous and symmetric lesion of the cavernous sinuses, without any other encephalic or meningeal lesions, raised the hypothesis of a paraneoplastic origin. A plausible paraneoplastic link between the neuro-ophthalmological lesion and the malignant disorder is IgG4-related disease, a condition that may be associated with lymphoma. As in our case, this diagnosis is often presumptive because histopathological confirmation is difficult to obtain.